Investigation of the potential curative effects of Gui-Zhi-Jia-Ge-Gen decoction on wind-cold type of common cold using multidimensional analysis. (15th November 2022) - Wan, Xinhao; Wu, Wenting; Zang, Zhenzhong; Li, Kang; Naeem, Abid; Zhu, Yulu; Chen, Lihua; Zhong, Lingyun; Zhu, Weifeng; Guan, Yongmei
Abstract: Ethnopharmacological relevance: Gui-Zhi-Jia-Ge-Gen decoction (GJGD) is a classical Chinese medicine prescription that has been widely used in clinical practice for centuries. In recent times, TCM has received considerable attention for its potential efficacy in treating a wind-cold type of common cold. However, the effect of the Gui-Zhi-Jia-Ge-Gen decoction on the wind-cold type of common cold is still not fully understood, which presents challenges for both quality control, research and development. Furthermore, the identification of potential pharmacodynamic ingredients (PPIs) is important for developing quality control procedures for industrial and large-scale production. Aim of the study: The aim of this study was to investigate the potential curative effect of Gui-Zhi-Jia-Ge-Gen decoction on wind-type of common cold using multidimensional qualitative analysis that combined water-decoction spectrums, in vivo plasma spectrums, and molecular docking to identify key constituents of GJGD. Materials and methods: Water-based GJGDs were formulated according to the clinical usage documented in ancient medical texts. Ultra-high-performance liquid chromatography-quadrupole-time of flight mass spectrometry (UHPLC-Q-TOF-MS) was combined with computer-aided modeling screening to identify GJGD PPIs in rats following oral administration. Molecular docking experiments were carried out to predict the binding affinity of the PPIs to tumor necrosis factor α (TNF-α), interleukin 6 (IL-6), and interleukin-1β (IL-1β). Finally, the active ingredients of GJGD were further validated through pharmacodynamic experiments by assessing their efficacy in treating a wind-cold type of common cold in rats. Results: A total of 61 compounds were identified in the GJGD, 8 of which were detected in rat blood samples, providing stronger evidence for PPIs. Molecular docking also confirmed that these 8 compounds had a better affinity for TNF-α, IL-6, and IL-1β. In animal studies, various doses of the GJGD groups and the positive control groups caused significant elevations (P < 0.05) in the levels of white blood cell count and lymphocyte ratio and caused a significant decrease (P < 0.05) in the monocyte ratio and neutrophilic granulocyte ratio compared to the model group. Organ indexes of the GJGD treated groups were higher than the model group (P < 0.05). Significant neutrophil infiltration, hemorrhage, compensatory vacuole, and interstitium proliferation were observed in the lung tissue of the model group. However, the lung tissues of the various dose groups that received GJGD showed a near normal appearance, except for slight thickening, interstitium proliferation, and compensatory vacuole in some areas. The GJGD was found to be effective against a cold-wind type of common cold, which is in accordance with molecular docking studies suggesting that GJGD may be effective against a cold-wind type of common cold. Finally, based on multidimensional analysis, 8 potential compounds in GJGD were identified as PPIs (puerarin, 3′-hydroxy puerarin, 3′- methoxy puerarin, daidzin, cinnamic acid, paeoniflorin, liquiritin, and glycyrrhizic acid). Conclusion: The present study combined water decoction spectral analysis, molecular docking, and in vivo blood plasma spectrum analysis to develop a multidimensional qualitative approach for the development of GJGD and to assess its effectiveness in a wind type of common cold in Sprague Dawley rats. Meanwhile, 8 compounds in the GJGD were identified as PPIs in this study, which may be useful in developing quality standards for complex TCM prescriptions. Graphical abstract: Image 1 Highlights: Gui-Zhi-Jia-Ge-Gen Decoction (GJGD) is one of the most well-known Traditional Chinese Medicine (TCM) prescriptions. GJGD was evaluated on a multidimensional basis to determine its potential efficacy in treating common cold. Nine potential compounds in the GJGD were identified as PPIs (potential pharmacodynamic ingredients). Molecular docking experiments confirmed the effects of PPIs on disease targets. GJGD is effective in treating a wind-cold type of common cold.